Randomized controlled within-subject evaluation of digital and conventional workflows for the fabrication of lithium disilicate single crowns. Part I: digital versus conventional unilateral impressions - Benic, Goran I.; Mühlemann, Sven; Fehmer, Vincent; Hämmerle, Christoph H.F.; Sailer, Irena (The Journal of prosthetic dentistry, 2016)
Trials comparing the overall performance of fully digital and conventional workflows in reconstructive dentistry are needed. The purpose of the first part of this randomized controlled clinical trial was to determine whether optical impressions produce different results from conventional impressions with respect to time efficiency and patient and operator perceptions of the clinical workflow. Three digital impressions and 1 conventional impression were made in each of 10 participants according to a randomly generated sequence. The digital systems were Lava COS, iTero, and Cerec Bluecam. The conventional impression was made with the closed-mouth technique and polyvinyl siloxane material. The time needed for powdering, impressions, and interocclusal record was recorded. Patient and clinician perceptions of the procedures were rated by means of visual analog scales. The paired t test with Bonferroni correction was applied to detect differences (α=.05/6=.0083). The mean total working time ±standard deviation amounted to 260 ±66 seconds for the conventional impression, 493 ±193 seconds for Lava, 372 ±126 seconds for iTero, and 357 ±55 seconds for Cerec. The total working time for the conventional impression was significantly lower than that for Lava and Cerec. With regard to the working time without powdering, the differences between the methods were not statistically significant. The patient rating (very uncomfortable=0; comfortable=100) measured 61 ±34 for conventional impression, 71 ±18 for Lava, 66 ±20 for iTero, and 48 ±18 for Cerec. The differences were not statistically significant. The clinician rating (simple=0; very difficult=100) was 13 ±13 for the conventional impression, 54 ±27 for Lava, 22 ±11 for iTero, and 36 ±23 for Cerec. The differences between the conventional impression and Lava and between iTero and Lava were statistically significant. The conventional impression was more time-effective than the digital impressions. In terms of patient comfort, no differences were found between the conventional and the digital techniques. With respect to the clinician perception of difficulty, the conventional impression and the digital impression with iTero revealed more favorable outcomes than the digital impression with Lava.